Sustainable Economic Development: A Systematic Literature Review on Global Perspectives and Strategies - Doloan, Arisanjaya (Economics Studies and Banking Journal (DEMAND), 2024)
This research analyzes global factors that influence sustainable economic development strategies. Through a systematic literature review approach, factors considered include Foreign Direct Investment (FDI), international trade, cooperation between countries, climate change, and political uncertainty. The analysis results show that FDI, international trade and cooperation between countries have an important role in supporting sustainable economic growth. However, challenges from climate change and political uncertainty can hinder the implementation of sustainable economic development strategies. The complex interaction between these factors demands a deep and responsive understanding to achieve sustainable economic development goals in an ever-changing global era.